FRI0525 DURING ADIPOGENIC DIFFERENTIATION OF MSC ON MINERALIZED BONE FRAGMENTS: Visaftin-Mediated Osteodestructive Effects are Reduced. (June 2019) - Tsiklauri, Lali; Werner, Janina; Frommer, Klaus; Rehart, Stefan; Wenisch, Sabine; Müller-Ladner, Ulf; Neumann, Elena
Abstract : Background: Osteoporosis (OP), as an age-related disease, is characterized by bone loss, increased fracture risk and poor regeneration. During aging and OP bone marrow adiposity is increased due to a shift of osteogenic towards adipogenic differentiation of bone marrow mesenchymal stem cells (MSC). The differentiation of MSC into adipocytes or osteoblasts is an important determinant of bone structural integrity. It is known, that fatty tissue not simply functions as energy storage but is metabolically highly active. Therefore, adipocyte-derived factors such as adipokines might influence MSC differentiation. Objectives: The role of interactions between adipocyte-derived factors and MSC in the pathogenesis of OP is not fully elucidated. Thus, we analyzed the presence of the adipokine visfatin in bone tissue and its effects on MSC differentiation in standard culture vs. spongiosa. Methods: The spongiosa of femoral heads of patients with osteoarthritis (OA) after hip replacement surgery, or after osteoporotic femoral neck fracture were used for RNA- and MSC-isolation. Adipogenic MSC differentiation was performed with/without visfatin and its inhibitor Apo866 as well as SB203580 p38-MAPK inhibitor. For the transfer and differentiation of MSC on cancellous bone, bone fragments were purified and sterilized. Gene expression was measured by Realtime PCR. Protein production was evaluated by ELISA. Results: Elevated visfatin-level were observed in OP compared to non-osteoporotic OA bone. Visfatin-induced secretion of proinflammatory factors was lower during adipogenesis on cancellous bone then in standard cell culture (e.g. 14d IL6, x-fold: standard culture 151±110, spong. 40±30, n=7). Significantly elevated MMP13 mRNA as well as protein expression induced by visfatin could be detected during adipogenesis on spongiosa as well as in standard cell culture. However visfatin-mediated MMP13 expression was markedly reduced in the presence of cancellous bone (e.g. 21d, x-fold: standard culture 81±89, spong. 13±21, n=7). Inhibition of visfatin by Apo866 decreased the visfatin-induced cytokine release but not the MMP13 expression during adipogenesis in culture (n=4). In contrast to Apo866, the p38-MAPK inhibitor did not influence cytokine release but reduced MMP13 expression in a time dependent manner. Conclusion: Visfatin level was elevated in osteoporotic vs OA bone. Therefore, visfatin-mediated increase of MMPs and proinflammatory cytokines during adipogenic differentiation might influence bone turnover at the adipose tissue/bone interface. Our results support the idea that the extracellular matrix attenuates visfatin-mediated detrimental effects during adipogenesis. The observed visfatin-mediated effects most likely depend on different signaling pathways. Disclosure of Interests: Lali Tsiklauri: None declared, Janina Werner: None declared, Klaus Frommer: None declared, Stefan Rehart: None declared, Sabine Wenisch: None declared, Ulf Müller-Ladner Grant/research support from: supported by an unrestricted educational grant from Celgene GmbH., Elena Neumann: None declared